Team-based learning versus traditional teaching effect on pharmacy Students' Performance: A systematic review and Meta-Analysis - Ghazwa B. Korayem; Albandari A. Alghamdi; Ohoud Aljuhani; Delaney Ivy; Alaa A. Alhubaishi; Hadeel Alkofide (Elsevier, 2024)
Background: Several pharmacy schools have implemented team-based learning (TBL) in their curriculum worldwide. Yet, TBL's effectiveness compared to traditional teaching in improving students' outcomes in pharmacy education is yet to be assessed collectively. Thus, the aim of this meta-analysis is to compare the performance of pharmacy students following the implementation of team-based learning (TBL) in the pharmacy curriculum as opposed to traditional learning methods. Methods: This systematic review and meta-analysis included studies that assessed students' performance after TBL was implemented in a pharmacy curriculum. Adhering to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines, the review conducted searches in Embase, MEDLINE, and Google Scholar until July 26, 2023. Results: A total of 11 studies comparing TBL against traditional teaching methods and assessing students' performance were included. The pooled analysis, involving 2,400 students from 10 studies, demonstrated a mean difference (MD) in favor of TBL (MD = 2.27, 95 % CI [-0.85, 5.40]). However, notable heterogeneity was observed with an I2 value of 82 %, and the observed difference did not reach statistical significance. Conclusion: TBL exhibited enhanced student performance in pharmacy education compared to traditional teaching, although the difference was not statistically significant. The meta-analysis findings support the use of TBL in pharmacy education for various pharmacy courses (pharmaceutical and clinical sciences courses) and students at different levels. However, there is a need for more robust studies to comprehensively evaluate TBL, considering aspects such as students' performance and engagement, skills development, and satisfaction.